PENGARUH KEKUATAN KELUARGA TERHADAP KINERJA MELALUI SISTEM PENGENDALIAN MANAJEMEN PADA PERUSAHAAN KELUARGA DI SURABAYA - Djoko Dewantoro (Jurnal Ekonomi dan Bisnis Airlangga, 2011)
By considering the number of family–businesses in Indonesia and especially the myth surrounds them, and then it is very interesting to empirically investigate it. This study determines the effect of family power through on the performance of family-businesses in Surabaya. Moreover, this study also argues that the effect will be mediated by management control systems before having an effect on the firm’s performance.With a total sample of 48 family-businesses, this study analyzes the data by using multiple regressions. The results indicated that family power significantly influences the management control system and performance of the company. Further results indicated that management control systems also significantly influence the company’s own performance. However, when this study analyzes family power and management control system as determinants of firm performance, the results indicated that management control system is not significantly influence the performance, while family power remains significant. In other words, the effect of family power on firm’s performance is not mediated by management control system. Theoretical and managerial implications are also presented. Keyword: Family Power, Management Control System, Performance, and Mediator